Coming to terms with myself: exploring the development of emerging white racial justice accomplices in college - Ash-Balá, Ellie, author; Muñoz, Susana, advisor; Barone, Ryan, committee member; Jackson, Jessica, committee member; Poon, OiYan, committee member (Colorado State University. Libraries, 2023)
Many of the conversations about diversity, equity, and inclusion in higher education rightly focus on the experiences of BIPOC (Black, Indigenous, and People of Color) students and how to support them on their educational journey. Fewer of the conversations involve naming and interrogating the oppressive systems that cause these students to need additional support in the first place. Additionally, education scholars highlight the difficulty of engaging White students in conversations about race. When challenged, White students often get stuck in emotional turmoil—experiencing emotions such as guilt, fear, and defensiveness—and they spend the bulk of their energy trying to prove they are not racist instead of learning, growing, or fighting racism. The purpose of this study was to explore the experiences of White students and how they develop as White people committed to racial justice while in college, with a particular emphasis on navigating emotionality. This study employed a critical qualitative approach using constructivist grounded theory methodology. Informed by sensitizing concepts from critical whiteness studies and the literature on White emotionality, I generated a model for the development of emerging White accomplices. The model identifies five critical characteristics that make up the emerging accomplice mindset: curiosity, agency, empathy, acceptance of discomfort, and persistence in the journey. These characteristics empower and sustain White students as they develop in their commitment to racial justice and enable them to constructively navigate challenges they encounter. Insights gleaned from this study can inform educators as they seek to strategically empower White students to move through their guilt and insecurities to take actions as racial justice accomplices.
Keywords: racial justice ally; White students; critical whiteness studies; whiteness; white fragility